Understanding Customer Recommendation Intentions in Human-AI Collaborative Smart Vending Services Through Perceived Satisfaction - Aleen Miguel E. Bonquin; Allaiza Mariele C. Bataycan; Angelo Kian G. Bautista; Jan Calvin S. Bascones; Travis Jan B. De Guzman; Jayvie O. Guballo (Bright Institute, 2026)
This study aims to examine the mediating role of perceived satisfaction in the relationship between service quality and willingness to recommend in the context of a custom phone case vending machine. Despite the growing adoption of automated retail technologies, limited empirical studies have explored customer behavior in personalized vending services, particularly in emerging markets. Addressing this gap, the study employed a descriptive-correlational research design with 319 respondents from selected shopping malls (Robinsons Galleria, SM Fairview, and SM Aura). Data were analyzed using weighted mean, regression analysis, and Sobel test to assess both direct and indirect relationships among variables. The findings indicate that respondents reported high perceptions across all SERVQUAL dimensions (reliability, assurance, tangibles, empathy, and responsiveness), suggesting strong overall service performance. Perceived satisfaction (M = 4.36) and willingness to recommend (M = 4.38) were also rated highly, indicating positive customer evaluations and advocacy intentions. Mediation analysis revealed that perceived satisfaction partially mediates the relationship between service quality and willingness to recommend. This suggests that while service quality directly influences recommendation behavior, it also exerts an indirect effect through enhanced customer satisfaction. This study contributes to the extension of service quality and customer behavior models in automated retail contexts by demonstrating both direct and mediated effects of service quality on recommendation intention. Practically, the findings highlight the importance of maintaining high service standards and optimizing customer experience in vending-based retail systems to strengthen satisfaction and encourage positive word-of-mouth.